Effects of Two Levels of Protein Supplementation on Intake, Apparent Digestibility and Ammonia Nitrogen in Growing Goats Fed Ammoniated Crop By-Products - Serrato-Corona, J. Santos; Minor-Hinojosa, Tania I.; Garcia-Sanchez, Hector D.; Minor-Hinojosa, Andrea (Pakistan Journal of Nutrition, 2016)
Agroindustrial by-products have a tremendous potential as nutrient sources for ruminants in arid and semiarid areas. An experiment was conducted to evaluate the effects of two ammoniated crop by-products and two levels of protein supplementation on intake, ammonia nitrogen and apparent digestibility of DM in growing goats. Eight goats crossed with Alpine (16.8±0.85 kg BW) were randomly assigned to four groups in a replicated Latin Square design with a 2 x 2 factorial arrangement of treatments. Goats were individually fed and received forage at 2% body weight dry matter base plus 150 g of supplement daily. Body weight gain was higher in goats fed sorghum stubble (p = 0.01). Dry matter retention was higher in goats fed sorghum stubble (p = 0.04). Organic matter retention was affected by forage (p = 0.001). FND was similar between supplements, but goats fed sorghum stubble retained more FND (P = 0.01). No significant effect of CBP*SUP interaction was detected (p = 0.87). Ammonia nitrogen concentration (N-NH3) was higher in goats fed sorghum stubble (p = 0.006). Goats supplemented with WMS showed higher ammonia nitrogen concentration (p = 0.005). Interaction did not affect blood urea nitrogen concentration (p = 0.79). Blood urea nitrogen was higher in goats fed sorghum stubble (p = 0.01). Supplementation did not affect blood urea nitrogen concentration (p = 0.18). In conclusion, feeding ammoniated sorghum stubble plus supplementation based on poultry litter-sugarcane molasses, wheat middling’s and soybean meal is a suitable alternative during drought season for growing goats.